2020
DOI: 10.1109/access.2020.2975053
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Market Share Variation in Multi-Airport Area Incorporating Airport Choice Habit

Abstract: For the reason that passengers commonly need some time to change their habitual airport choice, the demand attracted by a newly conducted service of an airport may gradually increase at the startup time. We refer to this duration as the cultivation period and analyze the variation in the market share within the period by simulating the switch of habitual airport choice. Considering the effects of habit on passengers' cognitive risks, the cumulative prospect theory is applied to model the habitual airport choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Various studies have found that MAS development can promote the sustainable competitiveness of airports and regions [7][8][9]. While research on MAS has focused on multi-airport passenger markets [10][11][12][13], fewer studies have investigated multi-airport logistics markets. Shen first proposed the concept of MLS [4].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have found that MAS development can promote the sustainable competitiveness of airports and regions [7][8][9]. While research on MAS has focused on multi-airport passenger markets [10][11][12][13], fewer studies have investigated multi-airport logistics markets. Shen first proposed the concept of MLS [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…x i x 2 (13) x i indicates the cargo and mail throughput of i airport, and x is the total cargo and mail throughput of all airports in the urban agglomeration.…”
Section: Differentiation Characteristics Of Airport Logistics Resourcesmentioning
confidence: 99%
“…A multi-airport system is a set of airports that serves the airline traffic of a metropolitan area [17], which is a hot topic of research in the field of air transport. In recent years, research on multiairport systems has focused on the multi-airport passenger markets [18][19][20][21][22], the evolution of spatiotemporal dynamics [23,24], and the airspace management of multi-airport systems [25][26][27][28]. There is relatively limited literature on the multi-airport system from the perspective of logistics.…”
Section: Development Forecast Of Mlsmentioning
confidence: 99%